Synthesis, structural characterization and antitumor activity of new chromeno[4′,3′:4,5]thiopyrano[2,3-d]thiazole derivatives - Hoidyk, Mykhailo; Karkhut, Andriy; Polovkovych, Sviatoslav; Lesyk, Roman (ScienceRise: Pharmaceutical Science, 2025)
The development of heterocyclic compounds with significant biological activity remains a priority in modern medicinal chemistry. The use of cascade domino reactions, such as Knoevenagel condensation combined with hetero-Diels-Alder cyclization, enables the efficient construction of complex structures with potential anticancer properties. The aim of the study. To synthesize a series of thiopyrano[2,3-d]thiazole derivatives via a cascade Knoevenagel–hetero-Diels–Alder reaction followed by N3-alkylation and evaluate their in vitro antitumor activity in the NCI-60 human cancer cell line panel. Materials and methods. Structural identification of the compounds was carried out using NMR spectroscopy in DMSO-d₆ with tetramethylsilane (TMS) as the internal standard, and LC-MS analysis with an APCI mass-selective detector. Biological activity was assessed using the NCI-60 screening program, which includes a panel of 60 human cancer cell lines of various origins. Key parameters such as growth inhibition (GI₅₀), lethal concentration (LC₅₀), and cytotoxicity at micromolar concentrations were determined. Results. A series of thiopyrano[2,3-d]thiazole derivatives were synthesized through a two-step domino Knoevenagel condensation and intramolecular hetero-Diels–Alder cyclization between 4-thioxo-2-oxothiazolidinone and O-alkylated salicylaldehyde derivatives bearing allylic or propargyl substituents. Subsequent N3-alkylation yielded compounds 3.1 (60.0%), 3.2 (67.0%), and 4 (58.0%). Introduction of a piperidine moiety enabled the synthesis of water-soluble methanesulfonate salt 5 (70.0%). Reaction with 2,5-(2-propynyloxy)benzaldehyde led to in situ aromatization and the formation of a stable compound 8. Four compounds were tested for anticancer activity. Compound 8 showed the highest efficacy, causing complete cell death in OVCAR-4 (Ovarian Cancer, LC₅₀ = 29.5 μM) and strong growth inhibition in SR (Leukemia, GI₅₀ = 0.676 μM), 786-0 (Renal Cancer, GI₅₀ = 0.696 μM), A498 (Renal Cancer, GI₅₀ = 0.528 μM), and BT-549 (Breast Cancer, GI₅₀ = 0.666 μM) cells. Conclusions. The proposed synthetic methodology enables efficient preparation of structurally diverse thiopyrano[2,3-d]thiazole derivatives in high yields. N3-alkylation and incorporation of a piperidine fragment allowed for the synthesis of a water-soluble methanesulfonate salt 5. Among the tested compounds, compound 8 exhibited the most promising cytotoxicity and selectivity towards several cancer cell lines, suggesting its potential as a lead compound for further preclinical development of novel anticancer agents